A missed opportunity for Islamabad: Pakistan-American relations after the Abbottabad raid - Christian Wagner (Stiftung Wissenschaft und Politik (SWP), 2011)
The killing of Osama bin Laden by U.S. special forces on 2 May 2011 subjects the tense relationship between Pakistan and the United States to yet another stress test. At least in theory, presenting the raid as a joint success would have offered the chance to fundamentally improve bilateral relations, putting Pakistan in a position to reap immense political, military and economic rewards. Conversely, the way this opportunity was missed reveals just how dreadful the relationship has become and raises questions about where Pakistan's foreign policy is heading and what attitude it will adopt towards stabilisation in Afghanistan
Keywords: 320